PENGARUH BELANJA MODAL PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP PENDAPATAN PERKAPITA PADA PEMERINTAH KABUPATEN/KOTA PROVINSI RIAU - SAHALA PURBA (JURNAL ILMIAH SIMANTEK, 2019)
This study aims to determine and analyze whether the Capital Expenditure, Regional Original Income and Balancing Funds to Per capita Income. The population of this study is the Regency / City Government in Riau Province. The research method used is descriptive statistical analysis. The total population of this study was 12 regencies / cities using the census method obtained as many as 60 observational observational data from 2012 to 2016. The type of data used is secondary data. The results of this study prove that in terms of Capital Expenditures, Regional Original Revenues and Balancing Funds have a significant effect on Per Capita Revenues in Regencies / Cities in North Sumatra Province. Partially, Capital Expenditure and Balance Funding variables have a significant and significant effect on Per Capita Income, while Regional Original Income has a positive and significant effect on Per Capita Income in Regencies / Cities in North Sumatra Province.